2003
DOI: 10.1017/s1037291100002880
|View full text |Cite
|
Sign up to set email alerts
|

Support Requirements and Effects of Supervision on Telephone Counsellors

Abstract: The aim of this research was to examine the effects of the implementation of direct one-on-one supervision in a prominent telephone counselling organisation and the support requirements of their telephone counsellors. Ninety-three telephone counsellors participated in this research. The results showed that more experienced telephone counsellors were more satisfied than less experienced telephone counsellors with the support offered by the organisation. Furthermore, female telephone counsellors showed significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…Consistent with research to date (McNamara & Gillies, 2003;Mishara & Giroux, 1993;Rosenfield, 2002;Shier & Graham, 2011; this research illustrates the importance of staff having regular and accessible supervision in the form of shift supervision. The accessibility and timeliness of shift supervision rather than monthly group and personal supervision was found to be invaluable in supporting telephone counsellors.…”
Section: Supporting Telephone Counsellors' Subjective Wellbeingsupporting
confidence: 83%
See 3 more Smart Citations
“…Consistent with research to date (McNamara & Gillies, 2003;Mishara & Giroux, 1993;Rosenfield, 2002;Shier & Graham, 2011; this research illustrates the importance of staff having regular and accessible supervision in the form of shift supervision. The accessibility and timeliness of shift supervision rather than monthly group and personal supervision was found to be invaluable in supporting telephone counsellors.…”
Section: Supporting Telephone Counsellors' Subjective Wellbeingsupporting
confidence: 83%
“…First, consistent with extant research (Kinzel & Nanson, 2000;McNamara & Gillies, 2003), the participants in this study found the work of telephone counselling to be challenging at times. Rosenfield (1997) suggests two main characteristics of telephone counselling contribute to the difficulties experienced in performing this work; the callers' ability to end the call at any time and the absence of visual cues.…”
Section: Youth Counsellors' Experiences Of Telephone Counselling Worksupporting
confidence: 79%
See 2 more Smart Citations
“…Phone consultation was presented by crisis intervention and suicide prevention centers early in 1960s and it was the necessity, accessibility and cheapness of this method that led to the increasing use of such services [4]. Today, there are lots of phone consultation lines all over the world providing different services such child advice lines and other services [5].…”
Section: Introductionmentioning
confidence: 99%